Factors Affecting the Decision to Buy Electric Vehicle of the Consumer in Nonthaburi Province - Snongtaweeporn, Teeradej (Journal of Dhamma for Life, 2025)
The objectives of this research were to 1) study of demographic factors of those who decide to buy electric vehicles Nonthaburi Province 2) Study the level of marketing mix factors affecting consumers decision to buy electric vehicles in Nonthaburi Province 3) study the relationship between personal factors and marketing mix factors with the buying decisions of electric vehicles of consumers in Nonthaburi Province This research was quantitative research. The sample was 400 people. The instrument was questionnaire. The data analysis were frequency percentage, mean, standard deviation, hypothesis test by using Chi-Square Test and Logistic Binary Regression analysis. The results of the study found that the majority of respondents were female, age 25-34 years, private company employee, bachelor’s degree studies, monthly income less than 30,000 baht. The overall of marketing mix factors that influence consumers’ decision to buy electric vehicles in Nonthaburi Province was at a high level. When considering each aspect, it was found that the aspect with the highest average was the product and the aspect with lowest average was the marketing promotion. The hypothesis testing found that the personal factors in gender, occupation and education relates to the buying decision of electric vehicles of Nonthaburi Province consumers. The marketing mix factors in product affecting the buying decision of buying electric vehicles of the consumers statistically significant at .05 level. The marketing mix factors in price and service process affecting the decision of buying electric vehicles of the consumers in Nonthaburi Province statistically significant at .01 level.